2019
DOI: 10.1021/acs.jproteome.8b00947
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Fragmentation Improves the Identification of Peptides Cross-Linked by MS-Cleavable Reagents

Abstract: Cross-linking mass spectrometry (XLMS) is becoming increasingly popular, and current advances are widening the applicability of the technique so that it can be utilized by non-specialist laboratories. Specifically, the use of novel mass spectrometrycleavable (MS-cleavable) reagents dramatically reduces complexity of the data by providing i) characteristic reporter ions and ii) the mass of the individual peptides, rather than that of the cross-linked moiety. However, optimum acquisition strategies to obtain the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(114 citation statements)
references
References 31 publications
(74 reference statements)
6
108
0
Order By: Relevance
“…MS2-CID: CID collision energy 30%, MS2 resolution 30K, AGC target 5e4, maximum ion injection time 100 ms. MS2-ETD: MS2 resolution 30K, AGC target 1e5, maximum ion injection time 120 ms. MS3: MS2 isolation window 2m/z, collision energy 35%, AGC target 3e4, maximum ion injection time 90 ms). Settings recommended by Stieger et al 32 were used for stepped HCD methods (MS1 orbitrap resolution 60K, MS1 m/z scan range 375-1500, MS1 maximum injection time 50 ms, MS1 AGC target 5e5, dynamic exclusion 30 s with 10 ppm mass window, charge state exclusion <3+ or >8+, isolation window 1.6m/z, stepped HCD with normalised collision energies 21%, 27% and 33%, TopN N = 10 starting with the most intense MS1 signal, MS2 resolution 30K, MS2 maximum injection time 100 ms, MS2 AGC target 5e4). Fig.…”
Section: Methodsmentioning
confidence: 99%
“…MS2-CID: CID collision energy 30%, MS2 resolution 30K, AGC target 5e4, maximum ion injection time 100 ms. MS2-ETD: MS2 resolution 30K, AGC target 1e5, maximum ion injection time 120 ms. MS3: MS2 isolation window 2m/z, collision energy 35%, AGC target 3e4, maximum ion injection time 90 ms). Settings recommended by Stieger et al 32 were used for stepped HCD methods (MS1 orbitrap resolution 60K, MS1 m/z scan range 375-1500, MS1 maximum injection time 50 ms, MS1 AGC target 5e5, dynamic exclusion 30 s with 10 ppm mass window, charge state exclusion <3+ or >8+, isolation window 1.6m/z, stepped HCD with normalised collision energies 21%, 27% and 33%, TopN N = 10 starting with the most intense MS1 signal, MS2 resolution 30K, MS2 maximum injection time 100 ms, MS2 AGC target 5e4). Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Finally we estimated the correctness of the software calculated FDR rate of the obtained data, by separating cross-link hits found within the ribosomal shotgun proteins 9 and found within the human proteome from our searches using the combined database. As shown in Supplemental Figure 6, for XlinkX, the number of "wrong" cross-links from or to human proteins varies between 4 -8 % of the total hit number and is therefore in the expected range.…”
Section: Recovery Check On Cross-linked E Coli Ribosomementioning
confidence: 99%
“…We are aware that -by means of obtained absolute XL numbers -others have reported more unique cross-links (up to 766 unique links for E.coli ribosome using DSSO or DSBU and fractionation using SEC or SCX respectively 9,31 ). Enriching via an affinity tag may still be very advantageous in case of a complex matrix, as this would be the case for in vivo investigations.…”
Section: Recovery Check On Cross-linked E Coli Ribosomementioning
confidence: 99%
See 1 more Smart Citation
“…Our group has previously shown that the number of identified peptides, when using alternatives to trypsin, could largely be improved by a sequential combination with trypsin. This includes AspN, GluC, chymotrypsin, and elastase for the detection of cross-link sites 12 15 and elastase applied to S. pombe whole cell lysates. 14 The sequential digestion increased the number of identified cross-links up to 19-fold for the Taf4–12 complex compared to digesting with elastase alone.…”
mentioning
confidence: 99%